Langmuir-Blodgett films formed by continuously varying surface pressure. Characterization by IR spectroscopy and epifluorescence microscopy - Wang, Lin (Langmuir : the ACS journal of surfaces and colloids, 2007)
Monolayer films of phospholipids at the air-water interface have been transferred to solid substrates under conditions of continuously varying surface pressure, an approach termed COVASP. The molecular and supramolecular properties of the film constituents have been characterized with two complementary techniques. IR spectroscopy was used to monitor chain conformation as a function of transfer surface pressure. Results were compared to those from Langmuir films determined directly at the A/W interface by IR reflection-absorption spectroscopy (IRRAS). The methylene stretching frequencies for both proteated and acyl chain perdeuterated 1,2-dipalmitoylphosphatidylcholine (DPPC and DPPC-d62) in the transferred molecules indicate that the phospholipids retain at least, in part, their surface pressure-dependent chain-conformational order characteristics. The line widths of these modes are somewhat reduced, suggestive of slower rates of reorientational motion in the Langmuir-Blodgett (LB) films. Epifluorescence microscopy reveals a progressive condensation gradient, including nucleation and growth of probe-excluding condensed domains along the transfer line. DPPC condensation, observed along a single LB film, was qualitatively comparable to compression-driven condensation as observed in situ or in conventional LB films transferred at constant pressures. However, condensation along the compression isotherm in COVASP-LB films was reduced by 15-20% as compared to films equilibrated at different constant pressures, probably the result of kinetic differences in equilibration processes. As a preliminary demonstration of the utility of this new approach, the monolayer --> multilayer transition known to occur (Eur. Biophys. J. 2005, 34, 243) in a four-component model for pulmonary surfactant has been examined. IR parameters from both the lipid and the protein constituents of the film all indicate that the transition persists during the transfer process. This new approach for the study of transferred films will permit the efficient characterization of lipid-protein interactions and structural transitions occurring in pulmonary surfactant films subjected to dynamic compression